Of Blickets, Butterflies, and Baby Dinosaurs: Children’s Diagnostic Reasoning Across Domains - Weisberg, Deena Skolnick; Choi, Elysia; Sobel, David M. (Frontiers in Psychology, 2020)
The three studies presented here examine children’s ability to make diagnostic inferences about an interactive causal structure across different domains. Previous work has shown that children’s abilities to make diagnostic inferences about a physical system develops between the ages of 5 and 8. Experiments 1 (N = 242) and 2 (N = 112) replicate this work with 4- to 10-year-olds and demonstrate that this developmental trajectory is preserved when children reason about a closely matched biological system. Unlike Experiments 1 and 2, Experiment 3 (N = 110) demonstrates that children struggle to make similar inferences when presented with a parallel task about category membership in biology. These results suggest that children might have the basic capacity for diagnostic inference at relatively early ages, but that the content of the inference task might interfere with their ability to demonstrate such capacities.